Se il genere epidittico fosse insegnato / If epideictic speeches were taught - Sans, Benoît (Rivista Italiana di Filosofia del Linguaggio)
Among the speech genres defined by Aristotle, epideictic was the genre of consensus, unity and fraternity and, like the other genres, was taught through exercises. In this paper, assuming the hypothesis that the epideictic genre and its techniques could still be useful in modern societies, I remind of the teaching of this specific genre and the techniques acquired thanks to this practice; then I try to make suggestions to recreate such kind of rhetorical training for contemporary audiences.